Middle Bathonian Foraminifers from the Patcham Formation, Jumara Dome, Kachchh, western India - Gupta, S.; Singh, S. K. (Journal of Nepal Geological Society, 1996)
The Patcham Shell Limestone and Coral Limestone of Jumara Dome have yielded a rich foraminiferal assemblage including species of Garantella, Epistomina, Reinholdella, Pseudomarssonella, and Reyadhella. On this basis middle Bathonian age is assigned to the fossil yielding basal part (Patcham Shell - Coral Limestone) of the Jumara Dome.